2022
DOI: 10.1021/acsagscitech.2c00008
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Nanoscale Silica Induced Novel Morphological and Biochemical Stimulus Effects in Chilli (Capsicum annuum L.)

Abstract: Application of nanoscale materials in agriculture for various reasons, including plant nutrition, has been an interesting multidisciplinary research component. Among the plant nutrients, silica plays an important role as a quasi-essential nutrient besides enhancing resistance against disease and pests in the plant system. In the present investigation, we report the effects of foliar spray (field experiment) of varied concentrations (250, 500, and 750 ppm) of nanoscale silica (NSiO2) and osic acid (350, 700, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In contrast, neutral nanomaterials cannot penetrate lipid bilayers of plants . Nanosilica is converted into the insoluble silicic acid layer through polymerization, which mostly deposits beneath the leaf cuticle and in cell walls, where it tightens the cell wall to improve resistance to biotic and abiotic stresses in chili plants …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, neutral nanomaterials cannot penetrate lipid bilayers of plants . Nanosilica is converted into the insoluble silicic acid layer through polymerization, which mostly deposits beneath the leaf cuticle and in cell walls, where it tightens the cell wall to improve resistance to biotic and abiotic stresses in chili plants …”
Section: Resultsmentioning
confidence: 99%
“…46 Nanosilica is converted into the insoluble silicic acid layer through polymerization, which mostly deposits beneath the leaf cuticle and in cell walls, where it tightens the cell wall to improve resistance to biotic and abiotic stresses in chili plants. 47 3.1.6. Estimation of Si in Leaves of N-SiO 2 -Treated Plants.…”
Section: Effect Of N-sio 2 On Oxidative Stress Parametersmentioning
confidence: 99%
“…The antioxidant capacity (AOC) of chili fruit was measured by DPPH (1, 1-diphenyl-2-picrylhydrazyl) radical scavenging assay following the procedure described by Zellama et al [17]. Total β-carotene content (BCC) was measured by following the method described by Prasad et al [18] using a spectrophotometer (PD-303UV, APEL, Japan). The chili samples for measuring total carotenoid content (TCC) and chlorophyll content (Chl a and Chl b) were prepared via the González-Cortés et al [19] method.…”
Section: Biochemical Analysis For Nutritional Phytochemicalsmentioning
confidence: 99%
“…4,5 Therefore, it was reported that monosilicic acid, orthosilicic acid, and inorganic complex forms are the main forms of Si fertilizer at present and are being widely employed in rice cultivation. 6 Unfortunately, monosilicic acid and orthosilicic acid with higher solubility and absorption rates may induce potential phytotoxicity in plants. The disadvantage can be remedied through the use of nanotechnology in which nanoscale silicon has completely different particle size and surface area compared to natural silicon, thereby affecting its uptake and translocation in rice plants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 Similarly, Prasad et al found that the foliar application of SiNPs could increase the growth and yield of groundnut. 6 Our previous studies indicated that the pretreatment of SiNPs could alleviate cadmium (Cd) toxicity in rice suspension cells in a sizedependent manner by regulating the expression of Cd-and Sirelated genes. 10 Additionally, the addition of SiNPs could inhibit the uptake of arsenic (As) in rice cells by improving the mechanical force of cell walls and regulating As-related genes under As stress.…”
Section: ■ Introductionmentioning
confidence: 99%